2013
DOI: 10.1371/journal.pone.0069600
|View full text |Cite
|
Sign up to set email alerts
|

RecQL4 Helicase Amplification Is Involved in Human Breast Tumorigenesis

Abstract: Breast cancer occur both in hereditary and sporadic forms, and the later one comprises an overwhelming majority of breast cancer cases among women. Numerical and structural alterations involving chromosome 8, with loss of short arm (8p) and gain of long arm (8q), are frequently observed in breast cancer cells and tissues. In this study, we show that most of the human breast tumor cell lines examined display an over representation of 8q24, a chromosomal locus RecQL4 is regionally mapped to, and consequently, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 49 publications
(56 reference statements)
7
49
0
1
Order By: Relevance
“…It will be important to assess whether MYC modulates the activity of protein complexes (e.g., Treslin/ TopBP1/RecQL4) that influence Cdc45 loading and/or dictates the chromatin context (acetylation or other histone modifications). In turn, these studies could shed light on the significance of known interactions between MYC and some of these factors (e.g., TopBP1), and help understand the functional significance of certain cancer-associated mutations, like those found in RecQL4 (Fang et al 2013) (refer to the COSMIC database, cancer.sanger.ac.uk/cancergenome/ projects/cosmic). Similarly, understanding the molecular and functional relationship between MYC and Cdk-2 should provide important insights into how MYC regulates replication initiation, but most notably, on the possible connection between replication stress and senescence, which as of now, remains a mystery.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…It will be important to assess whether MYC modulates the activity of protein complexes (e.g., Treslin/ TopBP1/RecQL4) that influence Cdc45 loading and/or dictates the chromatin context (acetylation or other histone modifications). In turn, these studies could shed light on the significance of known interactions between MYC and some of these factors (e.g., TopBP1), and help understand the functional significance of certain cancer-associated mutations, like those found in RecQL4 (Fang et al 2013) (refer to the COSMIC database, cancer.sanger.ac.uk/cancergenome/ projects/cosmic). Similarly, understanding the molecular and functional relationship between MYC and Cdk-2 should provide important insights into how MYC regulates replication initiation, but most notably, on the possible connection between replication stress and senescence, which as of now, remains a mystery.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Although aberrant expression of RECQL4 has been reported in sporadic osteoblastoma (19), breast and prostate cancer cells and tissues (20,21), its prognostic and chemotherapeutic significance in gastric cancer are not known. In this study, we demonstrated RECQL4 expression is aberrantly elevated frequently in both clinical gastric cancer samples and tumor cell lines, and a higher RECQL4 expression renders the gastric cancer cells more resistance to cisplatin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A tumor-promoting function of RECQL4 has been widely described (21). For example, Fang et al (13) found that overexpression of RecQL4 due to gene amplification plays a critical role in human breast tumor progression, and Arora et al (22) demonstrated that shRNA-mediated RECQL4 suppression in MDA-MB453 breast cancer cells significantly inhibited in vitro clonogenic survival and in vivo tumorigenicity. Su et al (15) found that elevation of RECQL4 level was positively associated with the aggressiveness of prostate cancer both in vitro and in vivo, implying that RECQL4 plays critical roles in prostate-cancer carcinogenesis and is a valuable biomarker for this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the RECQL4 gene are associated with the rare type II Rothmund-Thomson syndrome, which has a propensity for osteosarcomas (11,12). Recent studies have shown that RECQL4 acts as a tumor-promotor in some cancers, such as osteosarcomas, prostate cancer, colorectal cancer, and breast cancer (13)(14)(15)(16)(17). Moreover, depletion of RECQL4 has been shown to significantly reduce the proliferation of cancer cells, promote apoptosis, and impair tumorgenicity in tumor-bearing mice (13,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation